A new species and a new record of Urytalpa Edwards, 1929 (Diptera: Keroplatidae) from China - Zhu, Yi; Huang, Junhao; Liu, Liwei; Qi, Lei; Wang, Yang; Wu, Hong; Wang, Qingyun (Zootaxa, 2024)
One new species and a new record of Urytalpa (Diptera: Keroplatidae: Keroplatinae), U. leigongshana sp. n. and U. yoshidai Uesugi, are described in this paper, which were collected from Guizhou and Sichuan, China. The molecular identification and morphological description of U. leigongshana are provided, together with the adult images of these two species. Furthermore, this paper also offers a worldwide distribution map and a checklist of this genus.